2015
DOI: 10.1016/j.apgeochem.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Origin of brines, salts and carbonate from shales of the Marcellus Formation: Evidence from geochemical and Sr isotope study of sequentially extracted fluids

Abstract: Fluids co-produced with methane from hydraulically fractured organic-rich shales of the Marcellus Formation (USA) are characterized by high total dissolved solids (TDS), including elevated levels of Ba, Sr and Br. To investigate the source and geologic history of these high-TDS fluids and their dissolved constituents, we carried out a series of sequential extraction experiments on dry-drilled cuttings extracted within, below and above the Marcellus Shale from a well in Tioga County, New York State. The experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 50 publications
(86 reference statements)
8
42
0
Order By: Relevance
“…Salts used were calcium chloride dehydrate (CaCl 2 ⁄ 2H 2 O), magnesium chloride hexahydrate (MgCl 2 ⁄ 6H 2 O), sodium chloride (NaCl), potassium chloride (KCl), strontium chloride hexahydrate (SrCl 2 ⁄ 6H 2 O), sodium bromide (NaBr), sodium bicarbonate (NaHCO3), sodium sulfate (Na 2 -SO 4 ). Br-is not an additive in hydraulic fracturing fluid, but was added in the form of NaBr-as microgram quantities of Br-have been observed in Marcellus Shale leaching experiments and can potentially be removed from the shale during fluid-rock interaction [26]. The synthetic fracturing fluid was stored in a Nalgene bottle and placed inside a nitrogen desiccator prior to use in order to prevent atmospheric alteration.…”
Section: Synthetic Fracturing Fluidmentioning
confidence: 99%
“…Salts used were calcium chloride dehydrate (CaCl 2 ⁄ 2H 2 O), magnesium chloride hexahydrate (MgCl 2 ⁄ 6H 2 O), sodium chloride (NaCl), potassium chloride (KCl), strontium chloride hexahydrate (SrCl 2 ⁄ 6H 2 O), sodium bromide (NaBr), sodium bicarbonate (NaHCO3), sodium sulfate (Na 2 -SO 4 ). Br-is not an additive in hydraulic fracturing fluid, but was added in the form of NaBr-as microgram quantities of Br-have been observed in Marcellus Shale leaching experiments and can potentially be removed from the shale during fluid-rock interaction [26]. The synthetic fracturing fluid was stored in a Nalgene bottle and placed inside a nitrogen desiccator prior to use in order to prevent atmospheric alteration.…”
Section: Synthetic Fracturing Fluidmentioning
confidence: 99%
“…Our results, and the concomitant differences in salinity (Figure S1b), potassium (Figure S1c), and strontium [ Stewart et al ., ], suggest different sources for brines in the Late and Early Paleozoic rocks. Although evaporite deposits younger than Silurian have not been encountered near the Appalachian Basin, about 4 km of Permian rock is estimated to have been removed from this area [ Reed et al ., ; Rowan , ].…”
Section: Discussionmentioning
confidence: 99%
“…The later brines have much less potassium than the earlier brines, a pattern also noted in Devonian brines in Ohio [ Breen et al ., ]. A similar division was found in strontium (Sr) isotope content between Upper and Lower Devonian brines in southwestern Pennsylvania [ Stewart et al ., ].…”
Section: Study Sitementioning
confidence: 99%
“…This conclusion is supported by the limited variability in the Cl/Br leach results from this study. Stewart et al (2015) also suggested that the composition of the formation water was affected by multiple processes, possibly including basin scale, tectonically-driven fluid flow. That process may account for the slightly lower 207 Pb/ 206 Pb in the leachate from the units below the Marcellus Shale compared to the units above (Fig.…”
Section: Depositional Environment and Diagenetic Historymentioning
confidence: 95%
“…Based on Cl concentrations from this study the water:rock interaction to produce flowback water would need to be closer to 1:36. Based on Na levels from sequential leachate data from the same cuttings samples, Stewart et al (2015) suggest a similar water:rock ratio of 1:50 would be required to produce typical late stage Marcellus Shale produced water. However, Stewart et al (2015) also conclude, based on multiple geochemical parameters from sequential leaching tests, that high-TDS produced water from the Marcellus Shale may not be from in-situ reactions within the hydrofracturing zone but rather is liberated formation water from elsewhere within the Marcellus Shale, or from adjacent units.…”
Section: Depositional Environment and Diagenetic Historymentioning
confidence: 98%